2017
DOI: 10.1016/j.envint.2017.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Associations between urinary diphenyl phosphate and thyroid function

Abstract: Triphenyl phosphate (TPHP) is a commonly used organophosphate flame retardant and plasticizer with widespread human exposure. Data on health effects of TPHP are limited. Recent toxicological studies suggest TPHP may alter thyroid function. We used repeated measures to assess the temporal variability in urinary concentrations of the TPHP metabolite, diphenyl phosphate (DPHP), and to examine relationships between DPHP concentrations and thyroid hormones. We sampled 51 adults at months 1, 6, and 12 from 2010-2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 43 publications
(85 reference statements)
3
75
0
Order By: Relevance
“…6,11,1424,29 Descriptive studies were reported previously and are not discussed in detail here. Briefly, urine samples were collected in 2002–2015 and analyzed in 2009–2016.…”
Section: Methodsmentioning
confidence: 99%
“…6,11,1424,29 Descriptive studies were reported previously and are not discussed in detail here. Briefly, urine samples were collected in 2002–2015 and analyzed in 2009–2016.…”
Section: Methodsmentioning
confidence: 99%
“…Specific gravity corrected urinary DPHP ranged from nondetectable (< 0.06 µg/L) to 9.84 (median 0.27 µg/L, 95th percentile 2.65 µg/L) in the study from which these men were a subset [Meeker et al 2013b]. Another study found a significant 0.43 µg/dL increase in mean total T4 serum concentrations in individuals with specific gravity corrected urine DPHP concentrations greater than or equal to 2.65 µg/L compared to those with concentrations below 2.65 µg/L [Preston et al 2017].…”
Section: Biological Burden Of Flame Retardants: Urinementioning
confidence: 84%
“…Increasing evidence suggests that some OP triester FRs may have an impact on the thyroid system, and known metabolite products have been identified for several congeners including e.g. diester and para-OH triester conjugates in the case of TPHP (Farhat et al, 2013;Meeker and Stapleton, 2010;Preston et al, 2017;Su et al, 2015a). For this thesis project, a study set of four OP triester FRs was selected, including TDCIPP, TEP, TBOEP, TPHP, as well as two known metabolites of TPHP, diphenyl phosphate (DPHP) and para-OH-TPHP.…”
Section: Rationale For the Research Projectmentioning
confidence: 99%
“…Increasing evidence suggests OP esters may impact the thyroid system, including recent studies on zebrafish (Kim et al, 2015;Wang et al, 2013;Xu et al, 2015) and chicken (Crump et al, 2012;Egloff et al, 2014;Farhat et al, 2014Farhat et al, , 2013. Additionally, biomonitoring studies of human urine and serum thyroid hormone (TH) levels have identified positive associations between triphenyl phosphate (TPHP) exposure and total thyroxine (T4) levels in women (Preston et al, 2017), as well as triiodothyronine (T3) levels in men (Meeker et al, 2013), based on urinary levels of the diester metabolite diphenyl phosphate (DPHP).…”
Section: Introductionmentioning
confidence: 99%